2012
DOI: 10.1038/bmt.2012.71
|View full text |Cite
|
Sign up to set email alerts
|

Comparing efficacy of reduced-toxicity allogeneic hematopoietic cell transplantation with conventional chemo-(immuno) therapy in patients with relapsed or refractory CLL: a Markov decision analysis

Abstract: Despite therapeutic advances, relapsed/refractory CLL, particularly after fludarabine-based regimens, remains a major challenge for which optimal therapy is undefined. No randomized comparative data exist to suggest the superiority of reduced-toxicity allogeneic hematopoietic cell transplantation (RT-allo-HCT) over conventional chemo-(immuno) therapy (CCIT). By using estimates from a systematic review and by meta-analysis of available published evidence, we constructed a Markov decision model to examine these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Three nonrandomized studies comparing allo-HCT versus nontransplant strategies provide evidence favoring the option of allo-HCT for relapsed or refractory CLL [31-33]. A Markov decision analysis published by Kharfan-Dabaja et al [31] demonstrated a better overall life expectancy favoring allo-HCT (35 versus 25 months).…”
Section: Methodsmentioning
confidence: 99%
“…Three nonrandomized studies comparing allo-HCT versus nontransplant strategies provide evidence favoring the option of allo-HCT for relapsed or refractory CLL [31-33]. A Markov decision analysis published by Kharfan-Dabaja et al [31] demonstrated a better overall life expectancy favoring allo-HCT (35 versus 25 months).…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Allogeneic hematopoietic cell transplantation is the only known treatment modality that can offer the possibility of cure in CLL in approximately 50% of cases. [13][14][15] However, the procedure has been traditionally associated with increased morbidity and mortality preceding the evolution of reduced intensity conditioning regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, allo-HCT using reducedintensity conditioning (RIC) is now offered to patients of advanced age or with associated comorbidities who would not have been otherwise eligible for this procedure previously [31,32]. The development of RIC regimens occurred around the time when targeted therapies were being introduced into practice; thus, combining these approaches in an attempt to improve outcomes was a logical approach to pursue.…”
Section: Rituximab In Allo-hct Conditioning Regimensmentioning
confidence: 99%